2016
DOI: 10.1089/adt.2016.742
|View full text |Cite
|
Sign up to set email alerts
|

Big Data Mining and Adverse Event Pattern Analysis in Clinical Drug Trials

Abstract: Drug adverse events (AEs) are a major health threat to patients seeking medical treatment and a significant barrier in drug discovery and development. AEs are now required to be submitted during clinical trials and can be extracted from (), a database of clinical studies around the world. By extracting drug and AE information from and structuring it into a database, drug-AEs could be established for future drug development and repositioning. To our knowledge, current AE databases contain mainly U.S. Food and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…2 The post-processing steps include regular expressions, and a dictionary-based approach for extracting certain elds as information was entered in various formats in published results. 3 Validation of the data acquired on ClinicalTrials.gov: The reliability of the data was ensured by checking the consistency of the number of clinical trial entries in the downloaded CSV le with the retrieved results.…”
Section: Data Processingmentioning
confidence: 99%
“…2 The post-processing steps include regular expressions, and a dictionary-based approach for extracting certain elds as information was entered in various formats in published results. 3 Validation of the data acquired on ClinicalTrials.gov: The reliability of the data was ensured by checking the consistency of the number of clinical trial entries in the downloaded CSV le with the retrieved results.…”
Section: Data Processingmentioning
confidence: 99%
“…The AEs extracted from these trials span across 26 AE categories. [19] The Big Data Challenges and Opportunities:-It has been always observed that arrival of any new technology brings along with it some challenges or limitations. Similarly, Big Data also has challenges and some shortcomings as below listed [20]:- Evidence of practical benefits of big data analytics is scarce  Methodological issues, such as data quality, data inconsistency and instability, limitations of observational studies, validation, analytical issues, and legal issues exist.…”
Section: A Data Survey Was Carried Out By Scorr Marketingmentioning
confidence: 99%
“…Drug-induced gastrointestinal toxicities (DI-GITs) are the most common category of adverse events (AEs) both during clinical trials 1 and after drug approval. 2 When incidence of druginduced AEs is broken down by individual symptoms, five GI AEs (nausea, vomiting, constipation, diarrhoea, and abdominal pain) rank among the 12 most frequent.…”
Section: Introductionmentioning
confidence: 99%
“…2 When incidence of druginduced AEs is broken down by individual symptoms, five GI AEs (nausea, vomiting, constipation, diarrhoea, and abdominal pain) rank among the 12 most frequent. 1 These AEs occur across all drug modalities and span all therapeutic areas. 3 However, the consequences of GIT often differ from those in other organ systems with respect to timing of discovery, medical response, impact on drug development, and effects on patients.…”
Section: Introductionmentioning
confidence: 99%